Prevalence of Gastrointestinal Protozoan Infections in Pigs of Dimapur District (Nagaland) and Its Treatment - Laha, R.; Goswami, A.; Das, M.; Patra, M. K.; Das, R. K.; Ebibeni, N.; Sen, A.; Deka, B. C. (Indian Journal of Hill Farming, 2018)
Rearing of pigs is one of the ways of livelihood of tribal population of north eastern region of India. But one of the major constraints of rearing of pigs is the gastro intestinal (GI) parasitic infections and pigs of different states of north eastern region have been found to be infected with high percentage of various GI parasites. Among GI parasites, GI protozoan infections cause reduced body weight gain and decreased haemoglobin concentration in infected pigs, that have generally received little attention. Some of the GI protozoan parasites of pigs have zoonotic significance also. Keeping in view of importance of GI protozoan infections of pigs, a study was undertaken to know the prevalence of GI protozoan infections in pigs of Dimapur District of the state Nagaland and to treat such infections. For this, a total of 142 numbers of faecal samples of pigs, maintained in both organized and unorganized ways, were collected. These faecal samples were examined microscopically to observe the presence of protozoan infections by direct and indirect methods. Among GI protozoan infections, overall 58.45% pigs were found as positive for Balantidium coli infections and 42.95% pigs were found as positive for Eimeria spp. infections. A combination of Metronidazole (@20 mg/kg. b.wt.) and Furazolidone (@10 mg/kg. b.wt.) or single Oxytetracycline @10 mg/kg. b.wt. orally consecutive for 4 days were found 100% effective for the treatment of B. coli infections in pigs. Amprolium (@ 45 mg/kg b.wt.) orally, for consecutive four days were found 100% effective for the treatment of Eimeria spp. infections in pigs. It can be concluded that GI protozoan parasitic infections particularly B.coli and Eimeria spp. are very much prevalent in pigs of Dimapur District of Nagaland and a combination of Metronidazole and Furazolidone or single Oxytetracycline orally consecutive for 4 days are very much effective for the treatment of B. coli infections in pigs. For the treatment of Eimeria spp. infections in pigs, use of Amprolium for consecutive four days are very much effective.